Association between occupational ionizing radiation exposure duration and the increased risk of dyslipidemia: evidence from a large group of radiation workers - Meimei Zhong; Meimei Zhong; Xiaowen Wang; Qifeng Li; Zhijia Wu; Zhijia Wu; Xiangyuan Huang; Xiangyuan Huang; Xinyue Li; Xinyue Li; Yiqing Lian; Yingyi Peng; et al. (Frontiers in Public Health)
BackgroundAlthough radiation workers’ exposure levels consistently remained below established safety thresholds, accumulating evidence demonstrates that chronic low-dose ionizing radiation exposure may still pose significant health risks to humans. We aimed to explore the relationship between the years of low-dose radiation work and dyslipidemia.MethodsWe collected occupational and physical examination data of 10,338 radiation workers from 1,200 workplaces during 2019–2020 in Guangdong Province, China. After controlling for social demographic and health behavior confounders, we used a mixed-effects model to assess the association of ionizing radiation exposure duration with blood lipid biomarkers as well as the prevalence of dyslipidemia. We further comprehensively evaluated the modifying effects of various demographic characteristics, health behavior factors, and air pollutant concentrations.ResultsWe found that participants with prolonged ionizing radiation exposure tended to have 8–40% higher levels of total cholesterol (TC) compared to those with < 10 years of exposure. The estimates were 9–23% for triglycerides (TG) and 5–26% for low-density lipoprotein cholesterol (LDL-C). Similar disparities were observed for the prevalence of overall dyslipidemia, abnormal TC or TG, hypercholesterolemia, hypertriglyceridemia, and high β-lipoproteinemia, with odds being 1.51–2.45 times higher in the group with > 30 years of ionizing radiation exposure compared to others. Our estimates further indicated greater effect estimates for prolonged ionizing radiation exposure and the prevalence of lipid abnormalities (p < 0.05) among the females, unmarried ones, and the workers with normal BMI.ConclusionThese findings suggest a deleterious effect of prolonged ionizing radiation exposure on lipid metabolism, with certain groups of workers being particularly vulnerable.